Moderasi Beragama Islam dan Barat - Anica, Anica (Jurnal Studi Agama, 2021)
As the creatures on the earth, humans are bounded to diversities. Diversities, including different religions, tribes, race, ethnicities, complexion and cultures are blessings from God the Almighty. Religions have been the key to problems that occur due to diversities. Religions bring up the values of humanity and are against violence, oppression, radicalism, terrorism, intolerance, and any extreme actions regarding humanity issues of religious community. This article was qualitatively written based on content analysis on current religious moderation issues written and disseminated through mass media regarding Islam and the Western community. Results showed that religious moderation required the strengthening of the aspects of life among religious communities in any part of the world. Religious moderation would eventually bring peace and unity between Islam community and western community. Therefore, it is necessary that every element of the community from any nation, religion, race, tribe and culture bound themselves to the peace, harmony, equality, tolerance and act moderately in order to avoid conflicts and strengthen the unity. In addition, as a part of religious community, people need to collaborate to achieve those common goals.